Procyanidin B3 alleviates intervertebral disc degeneration via interaction with the TLR4/MD‐2 complex. Issue 6 (18th February 2020) - Shang, Ping; Tang, Qian; Hu, Zhichao; Huang, Shiyuan; Hu, Yuezheng; Zhu, Jianhong; Liu, Haixiao
Abstract: As a chronic musculoskeletal degeneration disease, intervertebral disc degeneration (IVDD) has been identified as a crucial cause for low back pain. This condition has a prevalence of 80% among adults without effective preventative therapy. Procyanidin B3 (Pro‐B3) is a procyanidin dimer, which is widely present in the human diet and has multiple functions, such as preventing inflammation. But the inhibiting effect of Pro‐B3 in IVDD development is still no known. Thus, our study aimed to demonstrate the therapeutical effect of Pro‐B3 in IVDD and explain the underlying mechanism. In vitro studies, human nucleus pulposus (NP) cells were isolated and exposed in lipopolysaccharide (LPS) to simulate IVDD development. Pro‐B3 pre‐treatment inhibited LPS‐induced production of inflammation correlated factors such as tumour necrosis factor α (TNF‐α), interleukin‐6 (IL‐6), prostaglandin E2 (PGE2) and Nitric oxide (NO). On the other hand, LPS‐medicated extracellular matrix (ECM) breakdown was blocked in Pro‐B3 treated NP cells. Additionally, Pro‐B3 treatment blocked the activation of NF‐κB/toll‐like receptor 4 pathway in LPS‐exposed NP cells. Mechanistically, Pro‐B3 could occupy MD‐2's hydrophobic pocket exhibiting high affinity for LPS to intervene LPS/TLR4/MD‐2 complex formation. In vivo, Pro‐B3 treatment prevented the loss of gelatin NP cells and structural damage of annulus fibrosus in rat IVDD model. In brief, Pro‐B3 is considered to be a treatment agent for IVDD.